Health Financing Policies in Jordan: The Allocation of Public Expenditures in Global Context - Rawabdeh, Ali A; Khassawneh, Anis S (Makara Journal of Health Research, 2018)
Background: This article aimed to clarify the adequacy of government financial resources toward furnishing the provision of efficient healthcare for fulfilling the health challenges in the light of worse economic scenario in Jordan. Methods: This analytical and prognostic study of healthcare spending in Jordan focuses on the public sectors that finance healthcare. Hence, all the available studies and posted materials in the nearby and global levels were used to analyze the government abilities to proceed with presenting healthcare within the current constraints. Results: Our results revealed that, in any case, the Jordanian government is not organized to proceed or prepared to continue providing health services at the present trend: fast increase in demand over publicly funded services in the absence of efficiency gains. Conclusions: For the healthcare system to be significantly efficient and equitable, the cash burden of contributions ought to be progressive toward preserving long-term sustainability. There is a progressive impact of the reform on healthcare provision and finance systems once the contributor's expenses are used to construct it; however, these findings do not seem to be conclusive.